Immunological tolerance induced by in utero injection. Issue 1 (February 1983) - Barnes, R D; Pottinger, B E; Marston, J; Flecknell, P; Ward, R H; Kalter, S; Heberling, R L
Abstract : Intrauterine injection of human whole blood into rabbit and rhesus monkey fetuses was found to result in long lasting unresponsiveness to human serum albumin. Intrauterine injection of viable allogeneic bone marrow cells into rabbit fetuses was without any apparent harmful effect and also resulted in permanent unresponsiveness demonstrated by donor red cell survival studies. The implication of these findings in respect of using this approach towards the correction of certain inherited diseases in man is discussed.